2023
DOI: 10.1038/s41598-023-32546-z
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention with azelastine nasal spray may reduce viral load in SARS-CoV-2 infected patients

Abstract: With the changing epidemiology of COVID-19 and its impact on our daily lives, there is still an unmet need of COVID-19 therapies treating early infections to prevent progression. The current study was a randomized, parallel, double-blind, placebo-controlled trial. Ninety SARS-CoV-2 positive patients were randomized into 3 groups receiving placebo, 0.02% or 0.1% azelastine nasal spray for 11 days, during which viral loads were assessed by quantitative PCR. Investigators assessed patients’ status throughout the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(43 reference statements)
2
3
0
Order By: Relevance
“…However, the current study did not include azithromycin treatment for patients admitted to the Terrassa Hospital, precluding assessment of the role of combined prescriptions. Despite this, the protective effect of antihistamines is suggested by our results, which is also consistent with other reports in vitro [20] and after nasal administration [21].…”
Section: Discussionsupporting
confidence: 94%

COVID-19 in relation to chronic antihistamine prescription

Puigdellívol-Sánchez,
JUANES-GONZÁLEZ,
CALDERÓN-VALDIVIEZO
et al. 2024
Preprint
“…However, the current study did not include azithromycin treatment for patients admitted to the Terrassa Hospital, precluding assessment of the role of combined prescriptions. Despite this, the protective effect of antihistamines is suggested by our results, which is also consistent with other reports in vitro [20] and after nasal administration [21].…”
Section: Discussionsupporting
confidence: 94%

COVID-19 in relation to chronic antihistamine prescription

Puigdellívol-Sánchez,
JUANES-GONZÁLEZ,
CALDERÓN-VALDIVIEZO
et al. 2024
Preprint
“…We previously demonstrated the efficacy of azelastine-HCl and a commercial nasal spray containing azelastine-HCl against major variants of SARS-CoV-2 in vitro [18]. The in vivo effectiveness of the azelastine-containing nasal spray was confirmed by a subsequent clinical trial [11]. Here, we show the activity of azelastine-HCl against the omicron BA.1 variant that emerged later during the SARS-CoV-2 pandemic in both co-administration and a therapeutic setting.…”
Section: Discussionsupporting
confidence: 51%
“…It was previously shown, using in silico methods, that the approved drug azelastine-HCl has antiviral activity. Azelastine-HCL inhibited SARS-CoV-2 replication in in vitro assays, and a clinical study with a commercially available nasal spray containing azelastine-HCl demonstrated a reduction in the viral load of SARS-CoV-2 in the nasopharynx [11]. Here, we provide in vitro evidence for the antiviral activity of azelastine-HCl against unrelated common respiratory viruses.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations